Evaluation of the Hospital Emergency Service, in critical situations, through the inclusion of Resilience and the Sustainable Development Goals - Rodríguez, Mariela E. (2022)
Simulation, in health services, has become an important tool that has made it possible to replicate real scenarios that have a critical degree and thus have reliable information to obtain knowledge about the variables managed in an emergency. In the activity of a Hospital Emergency Service (HED), we can find active agents such as doctors, nurses, patients and passive ones such as medical rooms, beds, among others, interacting between them. HEDs have been overwhelmed by catastrophic events, such as those induced by COVID 19, in the last two years. In these situations, the availability of resources, due to the considerable reduction in health personnel and the excessive arrival of patients for care, implies that the emergency service has become inoperative. The recovery of this essential service is fundamental and a priority. For this reason, it is necessary to analyze the period of time for departments, after a catastrophe, to reach a stable state that allows them to adapt to the new workload, that is, to analyze how resilient the ED is. The present work shows the proposal of a research project for the modeling and simulation of an ED that supports the design and evaluation of a resilient service considering the infrastructures, resources and services that occur in an ED. The model must consider the organization and infrastructure capacity to support and recover from extreme situations, in order to provide and maintain its operation and services in an adequate manner. To achieve this objective, the normal service index and the ability to resist, restore and evolve in the face of future risks and threats will be measured. The design of the model will be integrated and participatory, and it will focus on people and communities, governed by the principles of sustainable development goals regarding Health and Wellbeing, Gender Equality, Industry, Innovation and Infrastructure.